Estudio de la dinámica del tejido linfoide en mucosas de pequeños rumiantes para su aplicación en el diagnóstico de scrapie - Gallardo, Mauro Julián (2023)
Transmissible Spongiform Encephalopathies (TSEs) are a group of neurodegenerative diseases\nproduced by prions that affect humans and different animal species. They have a chronic course, neurological manifestations and invariably end with the death of the affected\nindividuals, lacking treatment to date. Of all the animal TSEs, scrapie affects sheep and goats is\nthe most widespread animal TSE, reporting the highest number of new cases per year, and creates trade barriers for small ruminants. In Argentina, no cases of scrapie or other animal\nTSEs have been identified.\nThe diagnosis of TSEs is based on postmortem detection of abnormal prion protein (PrPSc) by\nimmunohistochemistry, Western blotting, or ELISA. In the case of scrapie, antemortem diagnosis of the disease is possible given the particular early accumulation of PrPSc in lymphoid\ntissue (LT). PrPSc accumulates in lymphoid follicles of tonsils, lymph nodes, and mucosal\nlymphatic organizations. Due to its easy access, the detection of PrPSc in the LT of the third eyelid has been proposed, also evaluating the detection in rectal mucosa biopsies.\nThe objective of this thesis was to determine if there are variations in the lymphoid tissue associated with easily accessible mucosa of sheep and goats in relation to their age, to evaluate\ntheir composition, and to obtain diagnostic tools for scrapie. For this, the diagnostic aptitude of\nbiopsy samples from the third eyelid and rectum of sheep and goats from the provinces of Buenos Aires and Salta, respectively, was evaluated and their cellular components were\ncharacterized. In turn, an anti-PrPC antibody was developed and an immunohistochemistry\n(IHC) technique was optimized to recognize this protein and PrPSc in samples from infected\nsheep and cattle.\nPostmortem mucosa samples were taken from the third eyelid and rectal mucosa (simulating a\nbiopsy), and the contralateral eyelid of 66 sheep (30 over and 36 under 18 months) and 54\ngoats. The terminal portion of the rectum and anus of 35 sheep were also collected. They were\nfixed in 10% formalin and subsequently processed for histological analysis. The bibliography considers samples suitable for diagnosis to be those that present a minimum of 6 lymphoid follicles. According to it, only 1.8% of the conjunctival samples and 39.4% of the rectal samples\nof sheep were suitable. Regarding goats, 5.4 and 61.1% of the third eyelid and rectal mucosa\nsamples respectively met the aptitude criteria for diagnosis of scrapie. In the histological evaluation of the contralateral eyelid, lymphoid tissue was found only in 16.7% of the sheep\nand 50% of the goats. On the other hand, in the study of the rectum and anus, lymphoid tissue\nwas observed immediately after the mucocutaneous junction (23 samples suitable for diagnosis/35 total), which would decrease its presence towards the cranium (6/35 of the\nsamples taken at 2 cm of the union were suitable). These results suggest that biopsy of the third eyelid would not be useful for the diagnosis of scrapie due to the scarce development of LT. On the other hand, a biopsy of the rectal mucosa would be useful, considering the presence of lymphoid tissue in sufficient quantity. No statistically significant differences were found\nbetween the two age groups evaluated (over and under 18 months), so age would not influence the aptitude of these samples. The IHC technique was useful for the characterization of cell populations of the immune\nsystem. CD21+, CD3+ and L1+ cells were detected in both species, with no differences in\nimmunolabeling patterns with respect to species or age. CD21+ cells were observed inside the\nlymphoid follicles mainly in the germinal centers. This was to be expected since it is a marker of dendritic cells and mature B lymphocytes, which have this location. There were significant\ndifferences in CD21 labeling between rectal and third eyelid samples from sheep, finding a proportion of densely packed lymphoid follicles with scarce or no presence of CD21+ cells in\nthird eyelid samples. Due to the differences found and the importance of the presence of CDF\n(CD21+) for the accumulation of PrPSc in the LT of infected animals, the presence of germinal\ncenters should be considered in determining the diagnostic aptitude of the samples for the\ndiagnosis of scrapie.\nCD3+ cells were observed with a mainly perifollicular distribution, consistent with the distribution of T lymphocytes. However, labeling was also demonstrated in cells from the follicles. L1+ cells were found in low numbers in interfollicular regions consistent with the\ndistribution of macrophages. This coincides with what has been described by other authors. From a recombinant PrPC\n, it was possible to produce an IgY antibody capable of detecting ovine\nPrPC and PrPSc by IHC in ovine and bovine tissues with scrapie and BSE. The immunostaining pattern observed in the tissues was similar to that obtained using commercial antibodies.\nIt was not possible to detect PrPC in lymphoid tissue fixed in 10% formalin with the antibody developed or with the commercial antibodies used, contrary to what was reported by other\nauthors. This would be related to the fixative and/or procedures performed, as well as the lower detection capacity of the antibodies used in this work.\nThe results of this work indicate that the presence of lymphoid tissue in the evaluated mucosa\nwould not be associated with the age of the sheep. In the palpebral mucosa it would have less development, being easily detectable in the rectum, immediately before the mucocutaneous\njunction. This would be the sample of choice in the event of implementing a scrapie preclinical\ndiagnosis strategy. The antibody developed could be useful in the future in assays for the diagnosis of animal TSEs. For this, future studies will be necessary in order to characterize\nconcentrations of work and inputs for developing.